ABNORMAL T WAVE INVERSIONS AND EXTREME QT PROLONGATION - Georgiev, Antonio; Janushevski Filip; Nikolov, Igor; Gavrilovska-Brzanov Aleksandra; Jovanovski Srceva, Marija; Ivanovski, Ognen (Faculty of Medicine, University Ss. Cyril and Methodius in Skopje, 2022)
Introduction: Cardiovascular diseases are the cause of sudden cardiac arrest. One of the leading causes of death is the occurrence of ventricular arrhythmias. Prompt evaluation, diagnosis and management of ventricular arrhythmias are life-saving for these patients. Case report: We present the case of a 70-year-old female patient with neurological sensorimotor polyneuropathy with quadriparesis and verified chronic renal failure (CRF) gr. IV admitted at the University Clinic for Nephrology for acute renal failure. After hemodialysis treatment, she developed arrhythmogenic disability such as episodes of ventricular fibrillation (VF) and ventricular tachycardia (VT). The onset of VT/VF required pharmacologic and shock therapy treatment. Electrocardiogram (ECG) at presentation upon admission to the cardiology clinic was with abnormal T wave and QT inversions. We did not find any electrolytic disturbances or echocardiographic abnormalities in search for ischemia segment wall changes. Coronary angiography showed no significant lesions of the coronary arteries. Our strategy for treating this long QT interval was temporary pacing with high doses of b-blockers. According to the good response to the therapy, the patient got permanent pacing therapy (AAIDDD mode) and till this day she is still safe from occurrence of ventricular arrhythmias. Conclusion: Prolongation of ventricular repolarization in patients with long QT interval must be registered as a predictor of occurrence of ventricular arrhythmias